2006
DOI: 10.1038/sj.bjp.0706933
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a selective and potent antagonist of human P2X7 receptors, AZ11645373

Abstract: Background and purpose: The ATP-gated P2X 7 receptor has been shown to play a role in several inflammatory processes, making it an attractive target for anti-inflammatory drug discovery. We have recently identified a novel set of cyclic imide compounds that inhibited P2X 7 receptor-mediated dye uptake in human macrophage THP-1 cells. In this study the actions and selectivity of one of these compounds, AZ11645373, were characterized. Experimental approach: We measured membrane currents, calcium influx, and YOPR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
88
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(96 citation statements)
references
References 39 publications
4
88
1
2
Order By: Relevance
“…1d). These compounds have been demonstrated to be potent, pIC 50 =7.3 for plasma membrane pore formation in THP-1 cells [22], and selective for P2X7R [23]. These results provide further evidence for the important role of the P2X7R in the formation of functional multinucleated human osteoclasts.…”
Section: Introductionmentioning
confidence: 52%
“…1d). These compounds have been demonstrated to be potent, pIC 50 =7.3 for plasma membrane pore formation in THP-1 cells [22], and selective for P2X7R [23]. These results provide further evidence for the important role of the P2X7R in the formation of functional multinucleated human osteoclasts.…”
Section: Introductionmentioning
confidence: 52%
“…ATPinduced increase in the [Ca 21 ] c was significantly reduced by 1 lM AZ11645373 (Fig. 2C), a human P2X7 selective antagonist [37]. In contrast, ATP-induced Ca 21 response was completely insensitive to 10 lM 5-BDBD (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…More recently, Sharp et al reported that P2X 7 deficiency suppressed development of experimental autoimmune encephalomyelitis [44]. Therefore, P2X 7 receptors are promising targets in treatment of inflammatory diseases and pain regulation [45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%
“…The ATP analog 2′,3′-O-(4-benzoyl-benzoyl) ATP (BzATP) is more potent and produces higher maximal responses [50]. P2X 7 receptor activity is blocked by divalent cations and certain antagonists such as oxidized ATP, KN-62, and AZ11645373 that are relatively selective for the receptor [47,51]. However, the pharmacological profile of these agonists and antagonists shows striking species differences among human, rat, mouse, and guinea pig orthologs [4,50,52].…”
Section: Introductionmentioning
confidence: 99%